User in Motion to Please... - Lazić, Nikolaj (Array, 2007)
Increasing number of users wanting to access information services via their mobile devices demanded infrastructural changes of the Faculty of Humanities and Social Sciences network and services. Therefore, at the beginning of the year 2006 we have started the project Users in motion to please which was supposed to gather and transform the entire faculty’ s information services in order to respond to the users growing demands and to keep the pace with the technological changes. Our goal was to offer end-users (teachers, students, employees) easy access to information and information services even when they are “ in motion” i.e. accessing them via their mobile phones, PDAs, smartphones and laptops from the faculty or anywhere in the world. Certain phases of this project called for hardware-based changes (i.e. installation of numerous wireless access points in the Faculty buildings), while others have relied on minor software changes (i.e. adaptation of the information services interfaces – like webmail, CMS and so on), but the most important part of all these changes are security, access and privacy measures, most of them relying on introduction of the uniform system of authorization/authentication at the Faculty and University level. Information services that are modified and adapted during this project are: central web pages of the Faculty (online notice boards – departments’ news and announcements, announcement boards of the dean’ s office, online notice board of student administration service, online telephone directory), faculty-wide LMS called Omega, webmail service and library catalogue. The access to both wired and wireless network available in the open-access parts of the Faculty’ s buildings (hallways, libraries, classrooms) are enabled for authorized and authenticated users that have valid AAI@EduHr electronic identity issued by the faculty.